Re‐evaluation of the Edinburgh Postnatal Depression Scale as screening for post‐partum depression in Iwate Prefecture, Japan. Issue 9 (19th June 2019) - Sasaki, Yuri; Baba, Tsukasa; Oyama, Rie; Fukumoto, Kentaro; Haba, Gen; Sasaki, Makoto
Abstract: Aim: Although the Edinburgh Postnatal Depression Scale (EPDS) is widely used for screening for post‐partum depression (PPD), screening time point and cut‐off value in the current medical environment are not sufficiently examined. In this study, we examined appropriate timing and cut‐off value of EPDS for the diagnostic criteria of Diagnostic and Statistical Manual of Mental Disorders Fifth Edition. Methods: This study was a prospective cohort study of women who delivered at the Iwate Medical University Hospital from August 2016 to February 2019. The EPDS self‐assessment was conducted at 4 days and at 1 month after delivery (4D‐EPDS and 1M‐EPDS), and the Center for Epidemiologic Studies‐Depression scale (CES‐D) self‐assessment was conducted at 1 month after delivery (1M‐CES‐D) in eligible patients and the scores were tabulated. Participants were interviewed by a psychiatric specialist to identify PPD within 2 months after delivery. For each screening, a receiver operating characteristic analysis was performed to calculate the cut‐off value for PPD. Sensitivity, specificity, positive predictive value, negative predictive value and correct diagnostic rate were evaluated. Results: Of the 80 post‐partum women, PPD was found in nine cases (11.3%). The cut‐off values for PPD were ≥10 for 4D‐EPDS, ≥13 for 1M‐EPDS and ≥21 for 1M‐CES‐D. No significant difference was found in the sensitivity, positive predictive value or negative predictive value among the three screening methods. However, a significant difference was found in the specificity, and the correct diagnosis rate and these values were relatively higher in 1M‐EPDS. Conclusion: Based on the result of this Japanese cohort, 1M‐EPDS with a cut‐off value of ≥13 might be appropriate for PPD screening although that of ≥9 is currently employed.